The Economic Impact of a Switch From Prescription-Only to Non-prescription Drugs in Italy - Otto, Monica Hildegard; Pillarella, Carla; Jommi, Claudio (Frontiers in Pharmacology, 2018)
The paper analyses the potential economic impact of switching drugs from prescription-only to over the counter status, using Italy as a case-study. The study assumes a societal perspective, investigating the effects of switches (and consequent delisting) on drugs spending, avoided visits by GPs (General Practitioners) and avoided time spent by patients for these visits. It overcomes the main pitfalls of previous studies, providing a rational for listing switchable products and applying both a static (no impact of switch on prices and volumes consumed) and a dynamic approach (impact on pricing policies and volumes depending on price-elasticity). Different scenarios were assumed including shorter / longer time spent for visits and inclusion / exclusion of the economic value of time of retiree patients. Results show that switching policy provides with societal savings ranging from 1 to 2.1 1 billion Euro. The economic impact on patients is less straightforward and depends on the scenarios used. If a longer time is spent on visits, the economic value of this time will compensate the cost of the switch to patients due to delisting. Despite the net economic benefit should be carefully interpreted, the results demonstrate how switching can contribute to the sustainability of the health care system in the middle-long run thanks to the a more rational use of resources, combined with an increased awareness and responsibility of the involved stakeholders.